Multilayer film

CN118251307BActive Publication Date: 2026-11-03DOW GLOBAL TECHNOLOGIES LLC
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202180104215.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2026-11-03
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

Existing multilayer films lack enhanced mechanical properties and toughness in packaging applications, and are particularly prone to damage and tearing in heavy-duty transport bags.

Method used

A multilayer membrane structure is formed by a polyethylene-based polymer resin blend composed of LLDPE resin and LDPE resin catalyzed by Ziegler-Natta, comprising at least three polyolefin layers, with the outer and core layers composed of different polyolefin materials to improve the membrane's toughness and heat-sealing performance.

Benefits of technology

It achieves a balance between improved optical properties, toughness, and heat-sealing performance of multilayer films, enhances the mechanical properties of the film, and is suitable for packaging applications such as heavy-duty transport bags.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118251307B_ABST
    Figure CN118251307B_ABST
Patent Text Reader

Abstract

A multilayer film comprising at least three film layers comprising: (a) at least a first polyolefin film layer, wherein the first polyolefin film layer comprises a first outer film layer; (b) at least a second polyolefin film layer, wherein the second polyolefin film layer comprises a core film layer; and (c) at least a third polyolefin film layer, wherein the third polyolefin film layer comprises a second outer film layer; wherein the at least third polyolefin film layer is the same or different than the at least first polyolefin film layer; wherein the at least second core polyolefin film layer is disposed between and separates the first film layer from the third film layer; wherein the first, second, and third film layers are in contact together to form a multilayer film structure; wherein at least one of the polyolefin film layers of the three layer film structure is made from a polymer blend composition comprising: (i) at least a first ethylene-based polymeric resin; wherein the at least first ethylene-based polymeric resin comprises a catalyzed linear low density polyethylene having an altered molecular structure made using a Ziegler-Natta catalyst system 1, prepared as described in Preparation 1 in the specification; and (ii) at least a second ethylene-based polymeric resin; wherein the at least second ethylene-based polymeric resin comprises a low density polyethylene resin; and wherein the multilayer film comprising a catalyzed linear low density polyethylene having an altered molecular structure made using a Ziegeler-Natta catalyst system 1, prepared as described in Preparation 1 in the specification, exhibits at least a 10% improvement in puncture resistance compared to a multilayer film comprising a catalyzed linear low density polyethylene resin having an unaltered molecular structure made using a Ziegler-Natta catalyst; a method for making the multilayer film; and an article made from the multilayer film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to multilayer film structures, and more specifically, to polyethylene-based multilayer film structures with enhanced mechanical properties. The multilayer film structures of this invention can be used, for example, in packaging applications. Background Technology

[0002] To date, multilayer film products have been typically used in the packaging industry to manufacture packaging for large and heavy materials. Packaging made from multilayer films requires sufficient mechanical properties and withstandability to withstand the forces and loads borne by the packaging during transport and storage. Rigider and tougher films used for packaging (e.g., in heavy-duty transport bag applications) would benefit from increased packaging load capacity and improved impact / tear resistance.

[0003] Traditionally, some polyolefin resins used in the manufacture of multilayer films include conventional linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE). During multilayer manufacturing, LDPE is often blended with LLDPE to improve processability / bubble stability during production. Furthermore, LDPE can enhance the optical properties of multilayer films; however, it can also reduce physical properties, such as toughness. Therefore, the membrane manufacturing industry has been seeking multilayer film structures made from both LLDPE and LDPE resins that offer enhanced membrane properties, such as toughness, particularly for packaging applications.

[0004] A variety of known catalysts are typically used in the production of a wide range of LLDPE and HDPE products. Some known catalysts include Ziegler-Natta catalysts, chromium catalysts, single-point metallocene catalysts, and advanced unimodal and bimodal multicomponent catalysts. Many of these known catalysts are manufactured and supplied by Univation Technologies, LLC. Some of these known catalysts are described, for example, in WO2019241044; U.S. Patent No. 8,722,804B2; and U.S. Patent Application Publication No. 2013 / 0245201A1.

[0005] Some of the catalysts known above provide films with one or more improved properties, including improved optical properties such as reduced haze and / or increased transparency; and / or improved damage properties, such as improved dart impact resistance and / or improved tear resistance in the longitudinal (MD) or transverse (TD) direction as mentioned in WO2019241044; improved adhesion properties as mentioned in U.S. Patent No. 8,722,804B2; and improved TD tear resistance as mentioned in U.S. Patent Application Publication No. 2013 / 0245201A1. However, not all of the above catalysts are known to be used in the production of LLDPE for manufacturing multilayer films with enhanced film properties.

[0006] Therefore, it is desirable to provide a multilayer membrane structure exhibiting enhanced membrane performance characteristics; wherein the multilayer membrane structure has at least one membrane layer made of a polyethylene-based polymer resin blend composition comprising Ziegler-Natta catalyzed LLDPE resin and low-density polyethylene (LDPE) resin. Summary of the Invention

[0007] One general embodiment of the present invention relates to a multilayer film comprising at least three polyolefin layers: (a) at least a first polyolefin layer comprising a first outer film layer of the multilayer film; (b) at least a second polyolefin layer comprising a core film layer of the multilayer film; and (c) at least a third polyolefin layer comprising a second outer film layer of the multilayer film. The at least third polyolefin layer of the multilayer film may be the same as or different from the at least first polyolefin layer of the multilayer film. The at least second polyolefin layer comprising the core film layer of the multilayer film may be disposed between the at least first outer film layer and the at least third outer film layer of the multilayer film, and may be separated from the at least first outer film layer. The two outer film layers and the core film layer of the multilayer film are in contact with each other to form the multilayer film structure of the present invention.

[0008] In a preferred embodiment of the invention, a multilayer membrane structure having three or more polyolefin membrane layers is included; wherein at least one of the three or more polyolefin membrane layers of the multilayer membrane structure is made of a polyethylene-based polymer resin blend composition comprising: a Ziegler-Natta catalyzed LLDPE resin having an improved and / or optimized molecular structure as a first component; and an LDPE resin as a second component.

[0009] Another embodiment of the present invention includes a method for producing the above-mentioned multilayer film.

[0010] Another embodiment of the invention includes a packaging article made using the above-described multilayer film. For example, the packaging article may be a heavy-duty transport bag for packaging applications.

[0011] One object of the present invention is to produce a multilayer membrane structure having at least one membrane layer comprising a polyethylene-based polymer resin blend composition of (1) a performance-enhancing Ziegler-Natta catalyzed LLDPE resin and (2) an LDPE resin. When the above polyethylene-based polymer resin blend composition is incorporated into at least one polyolefin membrane layer of the multilayer membrane structure, the resulting polyolefin membrane layer of the multilayer membrane structure, made from the resin blend composition, advantageously and surprisingly provides a multilayer membrane with improved properties, including a combination and balance of improved optical, toughness, and thermal sealing properties of the multilayer membrane. Attached Figure Description

[0012] Figure 1 It is a schematic cross-sectional view of a multilayer membrane structure that includes three membrane layers.

[0013] Figure 2 It is a schematic cross-sectional view of a multilayer membrane structure comprising seven membrane layers. Detailed Implementation

[0014] Specific embodiments of the invention are described below. These embodiments are provided so that this disclosure is thorough and complete; and to fully convey the scope of the subject matter of the invention to those skilled in the art.

[0015] Unless otherwise stated, implied by the context, or customary in the art, all percentages, parts, ratios, etc., are based on or defined by weight. For example, unless otherwise indicated, all percentages mentioned herein are weight percentages (weight %).

[0016] All testing methods are current as of this disclosure.

[0017] All temperatures used in this article are in degrees Celsius (°C).

[0018] Unless otherwise stated, “room temperature (RT)” and / or “ambient temperature” in this document mean a temperature between 20°C and 26°C.

[0019] As used herein, the term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0020] The term “polymer” refers to a polymeric compound prepared by polymerizing monomers of the same or different types. The general term “polymer” therefore encompasses (1) the term “homopolymer,” which typically refers to a polymer prepared from only one type of monomer; and (2) the term “copolymer,” which refers to a polymer prepared from two or more different monomers. As used herein, the term “interpolymer” refers to a polymer prepared by polymerizing at least two different types of monomers. Therefore, the general term “interpolymer” includes copolymers or polymers prepared from more than two different types of monomers, such as trimers.

[0021] "Polyethylene" or "ethylene-based polymer" should mean a polymer comprising more than 50 mol% of units derived from ethylene monomers. This includes ethylene-based homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include, but are not limited to: low-density polyethylene (LDPE); linear low-density polyethylene (LLDPE); mono-site catalytic linear low-density polyethylene, including both linear low-density resins and substantially linear low-density resins (m-LLDPE); medium-density polyethylene (MDPE); and high-density polyethylene (HDPE). The "polyethylene" or "ethylene-based polymer" used in this invention has at least 50 wt% ethylene-derived units in one embodiment, at least 70 wt% ethylene-derived units in another embodiment, at least 80 wt% ethylene-derived units in yet another embodiment, and at least 90 wt% ethylene-derived units in yet another embodiment.

[0022] The term "LDPE" can also be referred to as "high-pressure ethylene polymer" or "highly branched polyethylene," and is defined as meaning that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator, such as a peroxide (see, for example, U.S. Patent No. 4,599,392, which is incorporated herein by reference). The density of LDPE resin is typically 0.916 g / cm³. 3 Up to 0.940 g / cm 3 Within the range.

[0023] The term "LLDPE" includes: resins produced using Ziegler-Natta catalyst systems and resins produced using mono-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphine imides, and geometry-restricted catalysts; and resins produced using post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also known as polyaryloxy ether catalysts). LLDPE includes linear, substantially linear, or heterogeneous ethylene-based copolymers. LLDPE contains fewer long-chain branchings than LDPE and comprises: substantially linear ethylene polymers, further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneous branched linear ethylene polymer compositions, such as those in U.S. Patent 3,645,992; heterogeneous branched ethylene polymers, such as those prepared according to the method disclosed in U.S. Patent 4,076,698; and blends thereof (such as those disclosed in U.S. Patents 3,914,342 and 5,854,045). LLDPE resins can be prepared via gas-phase, solution-phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0024] The term "MDPE" refers to a material with a density of 0.924 g / cm³. 3 Up to 0.942 g / cm 3 Polyethylene. “MDPE” is typically prepared using chromium or Ziegler-Natta catalysts or using single-point catalysts, including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly known as metallocenes), confined geometry catalysts, phosphine imine catalysts, and polyvalent aryloxy ether catalysts (commonly known as bisphenylphenoxy).

[0025] The term "HDPE" refers to a material with a density greater than approximately 0.935 g / cm³. 3 And at most about 0.980 g / cm 3 Polyethylene is generally prepared using Ziegler-Natta catalysts, chromium catalysts, or single-point catalysts (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly known as metallocenes), confined geometry catalysts, phosphine imine catalysts, and polyvalent aryloxy ether catalysts (commonly known as bisphenylphenoxy).

[0026] The term "ULDPE" refers to a material with a density of 0.855 g / cm³. 3 Up to 0.912 g / cm 3ULDPE refers to polyethylene with a density of 0.855 g / cm³, which is typically prepared using Ziegler-Natta catalysts, chromium catalysts, or single-point catalysts, including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly known as metallocenes), geometry-restricted catalysts, phosphine-imine catalysts, and polyvalent aryloxy ether catalysts (commonly known as diphenylphenoxys)). ULDPE includes, but is not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomers and plastomers typically have a density of 0.855 g / cm³. 3 Up to 0.912 g / cm 3 The density.

[0027] The terms "blend," "polymer blend," etc., in relation to polymer compositions refer to compositions of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase-separated. As determined by transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art, such blends may or may not contain one or more domain configurations. Blends are not laminates, but one or more layers of a laminate may contain blends. Such blends can be prepared as dry blends, in-situ formed (e.g., in a reactor), melt blends, or using other techniques known to those skilled in the art.

[0028] "Multilayer structure" or "multilayer film" refers to any structure having more than one layer. For example, a multilayer structure (e.g., a thin film) can have two, three, four, five, or more layers. A multilayer structure can be described as having layers represented by letters. For example, a three-layer structure designated A / B / C can have a core layer B and two outer layers A and C. Similarly, a structure having two core layers B and C and two outer layers A and D would be designated A / B / C / D.

[0029] The term "molecular weight distribution" has the same meaning as polydispersity index (PDI). The molecular weight distribution of a polymer resin is the ratio of its weight-average molecular weight (Mw) to its number-average molecular weight (Mn), i.e., Mw / Mn. Mw, Mn, and Mz can be measured using gel permeation chromatography (GPC), also known as size exclusion chromatography (SEC). The measurement of molecular weight by SEC is well known in the art.

[0030] The term “toughness” for membrane structures is used in this paper in relation to puncture resistance values ​​determined according to the procedures described in ASTM D5748-95.

[0031] The term “stiffness” in this article refers to the secant modulus of the membrane as determined according to the procedure described in ASTM D882-18.

[0032] In the context of the use of “modified or altered molecular structure (AMS)”, this document means LLDPE catalyzed by the Ziegler-Natta (ZN) catalyst or catalyst system described in WO2019241044A1.

[0033] The terms “comprising,” “including,” “having,” and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed using the term “comprising” may include any additional additives, adjuvants, or compounds, whether in polymeric or other forms. Conversely, the term “consistently comprising” excludes any other components, steps, or procedures (except those not essential to operability) from the scope of any subsequent statements. The term “consisting of” excludes any components, steps, or procedures not specifically described or listed. Unless otherwise stated, the term “or” refers to the listed members individually and in any combination. Use of the singular includes use of the plural, and vice versa.

[0034] The numerical ranges disclosed herein include all values ​​from the lower limit to the upper limit, and include both the lower limit and the upper limit. For a range containing definite values ​​(e.g., the range from 1 or 2 or 3 to 5 or 6 or 7), any subrange between any two definite values ​​is included (e.g., the range 1 to 7 above includes subranges of 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0035] As used throughout this specification, the abbreviations given below have the following meanings unless the context clearly indicates otherwise: "=" means "equal to" or "equal to"; "<" means "less than"; ">" means "greater than"; "≤" means "less than or equal to"; "≥" means "greater than or equal to"; "@" means "at"; "MT" = metric ton; g = gram; mg = milligram; Kg = kilogram; g / L = gram per liter; "g / cm 3 "g / cc" = grams per cubic centimeter; "kg / m³" = ... 3 = kg per cubic meter; ppm = parts per million weight; pbw = parts by weight; rpm = revolutions per minute; m = meter; mm = millimeter; cm = centimeter; μm = micrometer; min = minute; s = second; ms = millisecond; hr = hour; Pa = Pascal; MPa = megapascal; Pa-s = pascal-second; mPa-s = millipascal-second; g / mol = gram per mole; g / eq = gram per equivalent; M n =Number average molecular weight; M w =Weight-average molecular weight; M z =Z-mean molecular weight; pts = parts by weight; 1 / s or s -1= Countdown seconds [s] -1 ]; ℃ = degrees Celsius; psig = pounds per square inch; kPa = kilopascal; % = percentage; vol% = volume percentage; mol% = mole percentage; and wt% = weight percentage.

[0036] In one broad embodiment, the multilayer film of the present invention comprises at least three layers, including at least a first polyolefin layer, at least a second polyolefin layer, and at least a third polyolefin layer, wherein two or more of the first polyolefin layer, the second polyolefin layer, and the third polyolefin layer may be the same or different.

[0037] In some embodiments, each polyolefin layer constituting the multilayer membrane of the present invention is prepared from a polyolefin resin composition. In a preferred embodiment, the polyolefin resin composition of each polyolefin layer constituting the multilayer membrane of the present invention comprises at least one or more ethylene-based polymer resins. In another preferred embodiment, the ethylene-based polymer resin composition of each polyolefin layer constituting the multilayer membrane of the present invention comprises at least one or more LLDPE polymer resins. The LLDPE polymer resin of at least one of the at least three polyolefin layers used in the multilayer membrane comprises catalytically modified LLDPE. The catalytically modified LLDPE used in the present invention has a modified or altered molecular structure (AMS) that provides a multilayer membrane with improved or enhanced properties.

[0038] Catalyzed LLDPEs with AMS are typically prepared by catalyzing LLDPE resins using a Ziegler-Natta catalyst of some type that forms AMS-catalyzed LLDPEs. The Ziegler-Natta (ZN) catalyst for forming AMS-catalyzed LLDPEs is similar to other various ZN catalysts; however, the ZN catalyst used in this invention for forming AMS-catalyzed LLDPEs is separate and different from other ZN catalysts. Therefore, the ZN-catalyzed LLDPEs of this invention catalyzed with a variant of the ZN catalyst (described below) are referred to herein as “ZN-catalyzed AMS-LLDPE” or further abbreviated as “ZN-AMS-LLDPE” polymer resins.

[0039] In a preferred embodiment, the ZN catalyst used to prepare the ZN-AMS-LLDPE polymer resin composition comprises a Ziegler-Natta catalyst system 1, which is a ZN catalyst prepared as described in Preparation 1 below:

[0040] Preparation 1: Preparation of Ziegler-Natta catalyst system 1

[0041] Unbound by theory, it is believed that any ZN catalyst system described in WO 2019 / 241044 A1 can be used for use in methods of catalyzing LLDPE to form the ZN-AMS-LLDPE polymer resin of the present invention (also referred to as Resin B and Resin 1) without excessive experimentation. Ziegler-Natta catalyst system 1 is a catalyst or catalyst system for catalyzing LLDPE to form the ZN-AMS-LLDPE polymer resin.

[0042] Ziegler-Natta catalyst system 1 and its preparation are disclosed in Inventive Example 1a (IE 1a) of WO2019241044, except that the catalyst used to catalyze the LLDPE of the present invention (Ziegler-Natta catalyst system 1) is prepared on a commercial scale. According to Inventive Example IE 1a of WO2019241044, the synthesis of a spray-dried Ziegler-Natta pre-catalyst system is disclosed, which is the same catalyst as the catalyst used in the present invention (Ziegler-Natta catalyst system 1). Generally, the method for synthesizing the spray-dried Ziegler-Natta pre-catalyst system includes first preparing a spray-dried particulate solid consisting essentially of hydrophobic fumed silica, MgCl2, and THF using “Prep1” disclosed in WO2019241044. Then, 150 g of spray-dried granular solids, 520 g of mineral oil, and 8.7 g of Ti(OiPr)4 were mixed at 30 °C for 0.5 hours to produce an intermediate mixture, which consisted essentially of the spray-dried granular solids, mineral oil, and Ti(OiPr)4 or reaction products made from them. The intermediate mixture was free of dichloroethylaluminum (EADC). The intermediate mixture was then combined with 73.5 g of EADC at 30 °C for 2 hours to produce a spray-dried Ziegler-Natta pre-catalyst system of IE1a in mineral oil form.

[0043] Preparation 2: Preparation of ZN-AMS-LLDPE polymer resin

[0044] Typically, the ZN-AMS-LLDPE polymer resin used in this invention is prepared using the Ziegler-Natta catalyst system 1 (based on the catalyst disclosed in Example 1a (IE 1a) of WO2019241044) prepared above to catalyze LLDPE. In some embodiments, the Ziegler-Natta catalyst system 1 is injected into a gas-phase polymerization reactor in the presence of a compound, whereby the reactor contents undergo polymerization to form a polyethylene and butene copolymer, the compound being selected from the group consisting of ethylene, butene, hydrogen, nitrogen, isopentane, and mixtures thereof. The reaction is carried out under the polymerization reactor conditions described in Table I. The polyethylene and butene copolymer resin is then purged under nitrogen to remove residual hydrocarbons. The resin is then compounded with other components using a twin-screw extruder LCM100 and an underwater granulation cutter hub. The aforementioned other components added to the resin include, for example... 168 and Preblend 9K (both additives are available from BASF).

[0045] In another preferred embodiment, at least one of the at least three polyolefin layers of the multilayer film is formed from a resin blend of at least two or more polyolefin polymer resins. For example, in one preferred embodiment, the at least two or more polyolefin polymer resins used to form at least one of the three polyolefin layers of the multilayer film comprise a polymer blend composition of: (i) at least one of the ZN-AMS-LLDPE polymer resins described above; and (ii) at least one LDPE polymer resin.

[0046] When one of the three or more polyolefin layers of a multilayer film is formed by a blend of two or more polyolefin polymer resins comprising a combination of the following substances, one or more other remaining layers of the multilayer film may be formed by the same or different polymer resins: (1) at least one ZN-AMS-LLDPE resin (resin 1) and (2) at least one LDPE polymer resin (resin 2). For example, one or more other remaining layers of the multilayer membrane may be formed from at least one or more optional polymeric resins selected from the group consisting of: (i) ZN-AMS-LLDPE resin; (ii) another different Ziegler-Natta (ZN) catalyzed LLDPE resin (abbreviated herein as "ZN-LLDPE resin"); (iii) metallocene catalyzed LLDPE resin (abbreviated herein as "mLLDPE resin"); (iv) another different metallocene catalyzed LLDPE resin with long chain branching (LCB) (abbreviated herein as "mLLDPE-LCB resin"), which is a metallocene catalyzed LLDPE resin having an LCB value of 0.001 / 1000 carbon to <0.1 / 1000 carbon; (v) LDPE resin; (vi) VLDPE resin; (vii) ULDPE resin; (viii) MDPE resin; (ix) HDPE resin; (x) another different LLDPE resin; (xi) HDPE resin; and (xii) mixtures thereof.

[0047] The ZN-AMS-LLDPE resin (“Resin 1”) in the polymer resin blend composition for at least one layer of a multilayer film structure has the following characteristics:

[0048] (a) Butene comonomer is used in the preparation of ZN-AMS-LLDPE resin, and therefore the resulting polymer resin is a poly(ethylene-co-1-butene) copolymer resin;

[0049] (b) The density in a typical embodiment is 0.910 g / cm³. 3 Up to 0.935 g / cm 3 Alternatively, in another embodiment, it is 0.915 g / cm³. 3 Up to 0.925 g / cm 3 ; and alternatively, in another embodiment, it is 0.918 g / cm³. 3 Up to 0.922 g / cm 3 ;

[0050] (c) The melt index (specified as MI; I2, I2 or MI2) is from 0.8 g / 10 min to 2.8 g / 10 min in one general embodiment; alternatively, it is from 1.5 g / 10 min to 2.5 g / 10 min in another embodiment; and alternatively, it is from 1.7 g / 10 min to about 2.2 g / 10 min;

[0051] (d) Molecular weight distribution (Mw / Mn) in a general implementation is greater than (>) 3 to less than (<) 5;

[0052] (e)(Mz / Mw) is >2.5 to <5 in one general embodiment and >2.5 to <4 in another embodiment;

[0053] (f) CUMCDI is in the range of -1.0 to -0.1;

[0054] (g) wt% (93.0℃ to 120.0℃) / wt% (75℃ to 93.0℃) obtained by iCCD < 0.26;

[0055] (h) The molecular weight (Mw) (>93.0°C) obtained by iCCD analysis, divided by the total polymer, is <2.0 in one embodiment; <1.9 in another embodiment; and <1.7 in yet another embodiment; and

[0056] (i) The wt% (>93.0°C) obtained by iCCD in a general embodiment is in the range of 3% to 15%.

[0057] In addition to the characteristics (a) to (i) exhibited by the ZN-AMS-LLDPE resin as described above, the ZN-AMS-LLDPE resin may also have one or more of the following optional properties:

[0058] (j) The wt% (25.0°C to 37.0°C) obtained by iCCD is in the range of 2.0% to 8.0% in one general embodiment; and in the range of 3.0% to 7.0% in another embodiment;

[0059] (k) The wt% (75.0°C to 93.0°C) obtained by iCCD is greater than 41.5% in one general embodiment; >45% in another embodiment; and >46.0% in yet another embodiment;

[0060] (l) is produced by a gas-phase process using a Ziegler-Natta catalyst or catalyst system as described in WO2019241044; and

[0061] (m)ZN-AMS-LLDPE resin is produced by using "UNIPOL" TM Similar to the "PE method", it is prepared using a Ziegler-Natta type catalyst (available from Univin).

[0062] The LDPE resin (“Resin 2”) in the polymer resin blend composition for at least one layer of a multilayer film structure has the following characteristics:

[0063] (a) The density in a typical embodiment is from 0.915 g / cc to 0.927 g / cc; and

[0064] (b) Melt index, or I2, is from 0.8 g / 10 min to 2.5 g / 10 min in one general embodiment; alternatively, it is from 1.5 g / 10 min to 2.5 g / 10 min in another embodiment; and alternatively, it is from 1.8 g / 10 min to about 2.2 g / 10 min in yet another embodiment.

[0065] In addition to resins 1 and 2, the polymer resin blend composition may also include one or more optional polymer resins (“resin 3”), such as one or more of resins (i) to (xii) described above. Resin 1 and resin 2, and optionally resin 3, are used in at least one layer of the multilayer membrane structure. For example, other polyethylene resins, such as LLDPE resin, HDPE resin, and mixtures thereof, may be optionally included in the polymer resin blend composition for manufacturing the three layers described above. In other embodiments, optional additional layers may be added to the three-layer multilayer membrane structure; and one or more optional additional layers may include resins, namely any one, more than one, or all of resin 1, resin 2, and optional resin 3.

[0066] The polymer resin composition (resin 1, resin 2, and optionally resin 3) of each layer in the multilayer film of the present invention may optionally include any number of additional components, reagents, or additives. Therefore, one, two, or all of the polymer resin compositions used to form the layers of the multilayer film may include one or more optional components. For example, one or more other different polyolefin polymer resins may be added to the polymer resin compositions used to form the first, second, and / or third layers. In some embodiments, the optional polymer resin may be, for example, another LLDPE polymer resin different from resin 1, another LDPE polymer resin different from resin 2, a medium-density polyethylene (MDPE) polymer resin, and / or a high-density polyethylene (HDPE) polymer resin. In some embodiments, for example, having a concentration of 0.940 g / cm³... 3 Up to 0.980 g / cm 3 High-density polyethylene (HDPE) components with a density and melt index (I2) of 0.1 g / 10 min to 1.5 g / 10 min can be incorporated into the core layer of a multilayer membrane structure.

[0067] In other embodiments, the compositions used to form the first, second, and / or third layers may optionally contain one or more conventional additives, including, for example, lubricants, antioxidants, UV-promoted degradation inhibitors (“UV stabilizers”), hindered amine stabilizers, deacidifiers, nucleating agents, anti-caking agents such as silica or talc, processing aids, metal deactivators, dyes, pigments, colorants, antifogging agents, antistatic agents, plasticizers, viscosity stabilizers, hydrolytic stabilizers, UV absorbers, inorganic fillers, flame retardants, reinforcing agents such as glass fibers and glass sheets, synthetic (e.g., aramid) fibers or pulp, foaming agents, foaming agents, slip additives, release agents, tackifying resins, and combinations of two or more of these.

[0068] In some embodiments, the polymer resin compositions used to form the first, second, third, and combinations thereof may each include up to 5 wt% of any additional optional additives, based on the total weight of the respective layers. For example, the concentration of optional additives in the first, second, third, and combinations thereof may be 0 wt% to 5 wt% in one embodiment, 0.1 wt% to 5 wt% in another embodiment, and 0.5 wt% to 5 wt% in yet another embodiment, based on the total weight of the respective layers. The incorporation of optional additives can be achieved by any known process, such as by dry blending, by extruding a mixture of various components, by conventional masterbatch techniques, etc.

[0069] As an illustration of the invention and not a limitation thereof, a three-layer multilayer film structure comprising a surface layer, a core layer, and an inner layer can be produced using predetermined amounts / contents of resin 1 and resin 2; and optionally resin 3. For example, the surface layer of the three-layer multilayer film structure may include resin 1; and the content of resin 1 in the surface layer may be 30 wt% to 98 wt% in a general embodiment, alternatively 55 wt% to 95 wt% in another embodiment; and alternatively, from 85 wt% to about 95 wt% in yet another embodiment. For example, the core layer of the three-layer multilayer film structure may also include resin 1; and the content of resin 1 in the core layer may be 30 wt% to 100 wt%; alternatively, from 65 wt% to 100 wt% in another embodiment; and alternatively, from 85 wt% to about 100 wt% in yet another embodiment. For example, the inner layer of the 3-layer multilayer film structure may also include resin 1; and the content of resin 1 in the inner layer may be 30 wt% to 98 wt% in a general embodiment, alternatively 55 wt% to 95 wt% in another embodiment; and alternatively, 85 wt% to about 95 wt% in yet another embodiment.

[0070] Examples of resins that can be used in the resins (i)-(xii) described above in this invention may include, but are not limited to, the following resins:

[0071] (1) Zn-catalyzed LLDPE resin, such as ZN-LLDPE DFDA-7047 (available from Univin), has a viscosity of 0.918 g / cm³. 3 The density and melt index of 1 g / 10 min; and the use of Ziegler-Natta catalysts, such as UCAT. TM J catalyst (available from Univin) is approved by UNIPOL TM Poly(ethylene-co-1-butene) copolymer resin prepared by the "PE process";

[0072] (2) Another ZN-catalyzed LLDPE resin, such as ZN-LLDPE DFDA-7042 (available from Univin), has a concentration of 0.918 g / cm³. 3 The density and melt index of 2 g / 10 min; and the use of Ziegler-Natta catalysts, such as UCAT. TM J catalyst (available from Univin) via UNIPOL TM Another type of poly(ethylene-co-1-butene) copolymer resin prepared by PE process;

[0073] (3) mLLDPE resin, such as MCN-LLDPE HPR 1018HA (available from Univin), which has a strength of 0.918 g / cm³. 3The density and melt index of 1 g / 10 min; and the use of metallocene catalysts, such as XCAT. TM HP-100 catalyst (available from Univis) passed UNIPOL TM Poly(ethylene-co-1-hexene) copolymer resin prepared by PE process;

[0074] (4) HDPE resin, such as HDPE DGDZ-6095 (available from Univin), which has a strength of 0.948 g / cm³. 3 The density and flow index of 10 g / 10 min; and the use of chromium catalysts, such as ACCLAIM TM K-100 catalyst (available from Univis) was tested by UNIPOL. TM Another type of poly(ethylene-co-1-hexene) copolymer resin prepared by PE process;

[0075] (5) Another mLLDPE resin, such as EZ-LLDPE EZP 2703 (available from Univin), has a strength of 0.928 g / cm³. 3 The density and melt index are 0.3 g / 10 min; and a metallocene catalyst, such as XCAT, is used. TM EZ-100 catalyst (available from Univis) passed UNIPOL TM Poly(ethylene-co-1-hexene) copolymer resins prepared by PE process; and mLLDPE resins, such as EZ-LLDPE EZP 2703, having an LCB value of 0.001 / 1000 carbon to <0.1 / 1000 carbon;

[0076] (6) Another mLLDPE resin, such as EZ-LLDPE EZP 2010 (available from Univin), has a strength of 0.922 g / cm³. 3 The density and melt flow index are 1 g / 10 min; and a metallocene catalyst, such as XCAT, is used. TM EZ-100 catalyst (available from Univis) passed UNIPOL TM Poly(ethylene-co-1-hexene) copolymer resins prepared by PE process; and mLLDPE resins, such as EZ-LLDPE EZP 2010, having an LCB value of 0.001 / 1000 carbon to <0.1 / 1000 carbon;

[0077] (7) LDPE resin, such as LDPE 150E (available from Dow Chemical Company), has a content of 0.921 g / cm³. 3 Its density and melt flow index of 0.3 g / 10 min;

[0078] (8) LDPE resin, such as LDPE 450E (available from Dow Chemical Company), has a content of 0.923 g / cm³. 3 The density and melt index of 2 g / 10 min; and

[0079] (9) A mixture of any two or more of the above resins (1)-(8).

[0080] Reference Figure 1 This illustrates one embodiment of the multilayer membrane of the present invention, which is generally indicated by reference numeral 10. In one embodiment, the multilayer membrane 10 includes a multilayer membrane having at least three layers in the membrane structure 10. For example, in a preferred embodiment, the three-layer multilayer membrane 10 includes: (a) at least a first layer comprising at least a first outer polyolefin layer (skin layer or top layer), which is generally indicated by reference numeral 20; (b) at least a second layer comprising at least a core polyolefin layer (intermediate layer), which is generally indicated by reference numeral 30; and (c) at least a third layer comprising at least a second outer polyolefin layer (skin layer or bottom layer), which is generally indicated by reference numeral 40. The first outer layer 20 and the second outer layer 40 may be the same as or different from each other. Figure 1 As shown, the core polyolefin layer 30 is disposed between the first membrane layer 20 and the second membrane layer 40, that is, the core layer 30 is sandwiched between the two outer layers 20 and 40; and the first layer, the second layer and the third layer (membrane layers 20, 30 and 40 respectively) are in contact and bonded together to form a multilayer membrane structure 10.

[0081] The outer layers, including the first layer 20 and the third layer 40, may also be referred to as the "skin layer" or "outer layer." Outer layer 20 may also be referred to as the "top layer," and outer layer 40 may also be referred to as the "bottom layer." The core layer 30, including the second layer, may also be referred to as the "intermediate layer." In some embodiments, each of layers 20, 30, and 40 of the multilayer film of the present invention may be a single layer; and in another embodiment, each of layers 20, 30, and 40 of the multilayer film of the present invention may comprise a plurality of identical single layers or a combination of different single layers used to form the multilayer film. The term "core" or the phrase "core layer" refers to any inner layer of the multilayer film; and the phrase "skin layer" refers to the outermost layer of the multilayer film.

[0082] Figure 1 The multilayer membrane shown, comprising at least three membrane layers (layers 20, 30, and 40), can be designated as a layer A / B / C membrane structure, wherein outer layers 20 and 40 can be designated as A and C, respectively; and core layer 30 can be designated as B. In other embodiments of the three-layer membrane structure specified above, the outermost layers (layers A and C) of the multilayer membrane are in direct contact with core layer B. Figure 1In the embodiments of the present invention shown, each of the layers 20, 30, and 40 constituting the multilayer film is a single layer, indicated by reference numerals 21, 31, and 41.

[0083] refer to Figure 2 This illustrates another embodiment of the multilayer (e.g., two or more layers) film structure of the present invention, in which the multilayer film comprises at least seven layers; and these seven layers are used to form layers 20, 30, and 40. For example, each of layers 20, 30, and 40 includes a plurality of layers (or sublayers). Therefore, Figure 2 The resulting seven-layer multilayer membrane structure shown includes, for example, two membrane layers of membrane 20, three membrane layers of membrane 30, and two membrane layers of membrane 40. Figure 2 In the illustrated embodiment, layer 20 includes an outer layer 21 and an intermediate layer 22 disposed between the outer layer 21 and the core layer 30; and layer 40 includes an outer layer 41 and an intermediate layer 42 disposed between the outer layer 41 and the core layer 30. Furthermore, in Figure 2 In the middle, the core layer 30 includes a combination of a first core layer 31, a second core layer 32 and a third core layer 33, which is disposed between the outer layers 20 and 40.

[0084] Figure 2 The multilayer membrane shown, comprising at least seven membrane layers, can be designated as layers A / B / C / D / E / F / G, wherein outer layer 20 can be designated as membrane layers A and B; outer layer 40 can be designated as membrane layers F and G; and core layer 30 can be designated as membrane layers C, D, and E. In other embodiments of the above-designated seven-layer membrane structure, the outermost layers of the multilayer membrane, namely layers A and G, can each include inner layers B and F, wherein inner layers B and F are in direct contact with core layers C and E, respectively.

[0085] The multilayer film structure according to the present invention may include two or more layers. In a preferred embodiment, the multilayer film of the present invention has three or more layers. For example, the multilayer film structure of the present invention may include at least three layers in one embodiment (e.g., Figure 1 (as shown in the diagram); in another embodiment, it may include five layers; in yet another embodiment, it may include seven layers; and in yet another embodiment, it may include up to 13 or more layers. The number of layers in a multilayer film can depend on many factors, including, for example, the composition of each layer in the multilayer film, the desired properties of the multilayer film, the desired end application of the multilayer film, the fabrication process of the multilayer film, and other factors.

[0086] In a preferred embodiment, the multilayer membrane of the present invention is a three-layer membrane structure, which is designated as a membrane structure of layers A / B / C (respectively, layers 21, 31 and 41); wherein the first layer can be designated as A, the second layer can be designated as B, and the third layer can be designated as C.

[0087] In some embodiments, the second layer (layer B) may be referred to as the "core layer"; and the core layer may be a single layer or two or more single layers (i.e., a multilayer core layer). In some embodiments, one or both of the first layer (layer A) and the third layer (layer C) may be referred to as the "skin layer," "outer layer," or "inner layer"; and the first and third layers may be a single layer or two or more single layers (i.e., a multilayer outer or inner layer). In other embodiments, the first and third layers may be printable layers and / or sealable layers. For example, in some embodiments, both the first and third layers may be printable outer layers, or both layers may be sealable inner layers; and in other embodiments, the first layer may be a printable outer layer, and the third layer may be a sealable inner layer.

[0088] In some embodiments, the second layer (core layer) of the multilayer film may be positioned between the first and third layers. In other embodiments, the first and third layers may be the outermost layers of the multilayer film. As used herein, the outermost layer of a multilayer film can be understood to mean that there may be no other layer deposited above the outermost layer, such that the outer surface of the outermost layer is in direct contact with the surrounding air, and the inner surface of the outermost layer is in direct contact with the core layer. For example, the first and second layers and / or the third and second layers may be in direct contact with each other. As used herein, "direct contact" means that there may be no other layer positioned between the two layers in direct contact with each other.

[0089] In some embodiments, the multilayer film of the present invention may optionally further include one or more additional film layers (in addition to the first, second, and third layers). For example, the multilayer film of the present invention may optionally include one or more adhesive layers, wherein the adhesive layer is disposed between the first layer (outer layer) and the second layer (core layer); and / or wherein the adhesive layer is disposed between the second layer (core layer) and the third layer (another outer or inner layer).

[0090] In some embodiments, one or more additional optional membrane layers of the multilayer membrane structure of the present invention may be the same as or different from the first, second, and / or third layers. For example, in some embodiments, an optional additional fourth membrane layer may be included in combination with the three layers (first, second, and third layers) of the multilayer membrane structure described above. The optional additional fourth membrane layer and / or any optional additional membrane layer of the present invention (if used) may be a single-layer membrane or a multilayer membrane.

[0091] In a multilayer membrane structure, each layer provides a specific function or contributes certain properties to the overall multilayer membrane structure. The composition of the layers is selected based on the intended end-use application, cost considerations, etc. For example, layers can be used to provide specific structural or functional properties, such as increasing the volume of the structure, promoting interlayer adhesion, providing barrier properties, thermal properties, optical properties, sealing properties, chemical resistance, mechanical properties, damage resistance, etc. Therefore, in some embodiments, optional additional layers that can be used in the present invention may include, for example, an intermediate layer that promotes adhesion (also referred to as an adhesive layer); a barrier membrane that prevents water or other liquids, oxygen or other gases, light, and other elements from penetrating through the barrier membrane; a sealant membrane that participates in sealing the sealant membrane with itself or with another layer in the multilayer membrane; or combinations thereof. In a preferred embodiment, the multilayer membrane structure of the present invention may, for example, contain an adhesive layer and / or a sealant layer.

[0092] One or more optional additional membrane layers may be formed from polymeric resin compositions, such as polyethylene resins or blends of different polyethylene resins. Descriptions of polyethylenes that can be used to form the optional additional layers may include, but are not limited to, VLDPE resins, LDPE resins, other LLDPE resins, MDPE resins, HDPE resins, and combinations thereof. For example, in some embodiments, any layer of the multilayer membrane, such as the core layer, may include HDPE. HDPE may be incorporated into the core layer to increase its stiffness. In some applications, it may be important that the multilayer membrane has sufficient stiffness, as demonstrated by its tensile modulus, for example, to prevent deformation and breakage.

[0093] The thickness of each layer of the multilayer film, and the overall thickness of the multilayer film, is not particularly limited and can depend on many factors, including, for example, the number of layers in the multilayer film, the composition of the layers in the multilayer film, the desired properties of the multilayer film, the desired end-use application of the multilayer film, the manufacturing process of the multilayer film, and other factors, such as the die gap used during film casting or film blow molding. Therefore, the multilayer film of the present invention can have a variety of thicknesses. For example, in some embodiments, each layer of the multilayer film can have a thickness of less than 1,000 micrometers (μm or micron) in one general embodiment and less than 500 μm in another embodiment. In other embodiments, each layer of the multilayer film can have a thickness of 1 μm to 1,000 μm in one embodiment, 5 μm to 500 μm in another embodiment, and 5 μm to 100 μm in yet another embodiment.

[0094] The total thickness of the multilayer film can be less than 1,000 μm in one general embodiment and less than 500 μm in another embodiment. In other embodiments, the multilayer film can have a thickness of 1 μm to 1,000 μm in one embodiment, 5 μm to 500 μm in another embodiment, 10 μm to 500 μm in yet another embodiment, 15 μm to 500 μm in yet another embodiment, 5 μm to 100 μm in yet another embodiment, and 10 μm to 100 μm in yet another embodiment.

[0095] In some implementations, for various applications, such as packaging applications, especially when using smaller dimensions (“thickness reduction”), the multilayer polymer film of the present invention, and in some instances, the monolayer film used to make the multilayer film, has a balance of stiffness and toughness that allows for reduced material costs through thickness reduction (i.e., using a thinner film thickness).

[0096] In a broad embodiment, each of the at least three layers of the multilayer film of the present invention is formed of various resins; and in one embodiment, at least one of the three layers of the multilayer film (i.e., any one or more layers of the multilayer film structure) comprises a blend of two or more polyolefin polymer resins, wherein at least one layer of the multilayer film comprises a blend of polymer resins comprising (1) ZN-AMS-LLDPE resin and (2) LDPE resin, each resin being present at a predetermined concentration. For example, the outer polyolefin layer (the first layer of the multilayer film), the core polyolefin layer (the second layer of the multilayer film), and / or the sealant polyolefin layer (the third layer of the multilayer film) may comprise ZN-AMS-LLDPE resin (resin 1).

[0097] constitute Figure 1 and Figure 2 Each layer of the multilayer film of the present invention shown is prepared from a polyolefin resin composition; and in a preferred embodiment, each layer is prepared from at least one of the ethylene-based polymer resin compositions described above. In a general embodiment, the ethylene-based polymer resin composition for each layer of the multilayer film structure includes, for example, one or more LLDPEs in each layer, wherein at least one of the LLDPEs used in one or more layers constituting the multilayer film of the present invention is the ZN-AMS-LLDPE described above.

[0098] For example, in some implementation schemes, Figure 1The three-layer structure A / B / C of the multilayer film shown includes, for example, layers composed of polymer resin compositions: layer A (first film layer 21) is a polymer resin composition comprising a combination of resin 1, namely ZN-AMS-LLDPE resin, and resin 2, namely LDPE resin; layer B (second film layer 31) is a polymer resin composition comprising resin 1; and layer C (third film layer 41) is a polymer resin composition comprising a combination of resin 1 and resin 2.

[0099] In a general embodiment, the first layer of the multilayer film usable in the present invention may be a single layer or a combination of two or more single layers (i.e., a plurality of layers forming the first layer of the multilayer film). Furthermore, the first layer of the multilayer film usable in the present invention may be formed from a single polyolefin resin or a blend of two or more polyolefin resins. In one embodiment, the first layer of the multilayer film is formed from, for example, one or more ethylene-based polymer components. In other embodiments, the first layer of the multilayer film comprises a polymer resin blend composition usable for manufacturing a printable outer skin layer as the first layer.

[0100] In another embodiment, the first layer of the multilayer membrane is a combination or blend of two or more ethylene-based polymeric components selected from resins 1 and 2 described above, and optionally resin 3 selected from resins (i) to (xii) described above. For example, in another embodiment, the first layer of the multilayer membrane comprises a blend of polyethylene-based resins, such as a polymeric resin blend composition of a blend of resins 1 and 2. Other optional resins, i.e., resin 3, may, when used (if desired), be, for example, EZ-LLDPE resin; and / or HDPE resin.

[0101] In a preferred embodiment, the polymer resin blend composition for the first film layer of the multilayer film comprises a combination of resin 1 and resin 2. (See again) Figure 1 Each of the polymer resins (e.g., resin 1, resin 2, and optionally resin 3) in the polymer resin blend used to form the first polyolefin film layer 20 of the multilayer film 10 has a density within the range of 0.912 g / cm³ in one embodiment. 3 Up to 0.925 g / cm 3 In another implementation scheme, 0.915 g / cm³ 3 Up to 0.923 g / cm 3 And in yet another embodiment, 0.916 g / cm 3 Up to 0.922 g / cm 3The density of each polymer resin in the polymer resin is determined according to the procedure described in ASTM D 792-13.

[0102] Typically, each polymer resin in the blend of the resins used to form the first polyolefin film layer 20 of the multilayer film 10 (e.g., resin 1, resin 2, and optionally resin 3) has a melt index (I2) in the following ranges: in one embodiment, 0.5 g / 10 min to 2.5 g / 10 min; in yet another embodiment, 0.6 g / 10 min to 2.1 g / 10 min; in yet another embodiment, 0.8 g / 10 min to 1.5 g / 10 min; and in yet another embodiment, 0.9 g / 10 min to 1.2 g / 10 min. The melt index (I2) of each polymer resin is determined using the procedure described in ASTM D 1238-03 (at 190°C and using 2.16 kg weight).

[0103] Typically, each polymer resin (e.g., resin 1, resin 2, and optionally resin 3) in the blend of resins used to form the first polyolefin membrane layer 20 of the multilayer membrane 10 has a molecular weight distribution (Mw / Mn) within the following ranges: 2 to 6 in one embodiment; 3 to 5 in another embodiment; and 3.5 to 4.5 in yet another embodiment. The molecular weight (Mw) and molecular weight (Mn) of the LLDPE polymer are determined using gel permeation chromatography.

[0104] As an illustration of the invention and not limited thereto, in some embodiments, the polymer resin blend composition for manufacturing the first layer of a multilayer film comprises a polymer resin blend composition including a mixture of resin 1 and resin 2 as follows:

[0105] (1) Resin 1 comprises 30 wt% to 98 wt% in one embodiment, 55 wt% to 95 wt% in another embodiment, and 85 wt% to 95 wt% in yet another embodiment; and wherein resin 1 comprises ZN-AMS-LLDPE resin; and

[0106] (2) Resin 2 comprises 25 wt% to 2 wt% in one embodiment, 20 wt% to 5 wt% in another embodiment, and 15 wt% to 8 wt% in yet another embodiment, wherein resin 2 comprises LDPE resin.

[0107] In one general embodiment, the second film layer of the multilayer membrane used in the present invention can be a single layer or a combination of two or more single layers (i.e., a plurality of layers forming the second film layer of the multilayer membrane). Furthermore, the second film layer of the multilayer membrane used in the present invention can be formed from a single polyolefin resin or a blend of two or more polyolefin resins. In one embodiment, the second film layer of the multilayer membrane is formed from, for example, one or more ethylene-based polymer components. In another embodiment, the second layer of the multilayer membrane is the core layer of the multilayer membrane.

[0108] In another embodiment, the second layer of the multilayer membrane is a combination or blend of two or more ethylene-based polymeric components selected from resins 1 and 2 described above, and optionally resin 3 selected from resins (i) to (xii) described above. For example, in one embodiment, the second layer of the multilayer membrane comprises a blend of polyethylene-based resins, such as a polymeric resin blend composition of a blend of resins 1 and 2. Other optional resins that may be used, if desired, include, for example, resin 3, i.e., EZ-LLDPE resin; and / or HDPE resin.

[0109] In a preferred embodiment, the polymer resin used to form the second film layer of the multilayer film comprises a single resin. (See again...) Figure 1 The single ethylene-based polymer resin used to form the second polyolefin membrane layer 30 of the multilayer membrane 10 includes a catalytically catalyzed LLDPE resin, such as the optional resin 3 described above.

[0110] Typically, the polymer resin 3 used to form the second polyolefin membrane layer 30 of the multilayer membrane 10 has a molecular weight distribution (Mw / Mn) within the following ranges: 3 to 5 in one embodiment; and 3.5 to 4.5 in yet another embodiment. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the resin 3 are determined using high-temperature gel permeation chromatography.

[0111] As an illustration of the invention and not limited thereto, in some embodiments, the polymer resin used to manufacture the second layer of the multilayer film includes, for example, the polymer resin 3 described above; and the concentration of resin 3 is 30 wt% to 100 wt% in one embodiment, 65 wt% to 100 wt% in another embodiment, and 85 wt% to 100 wt% in yet another embodiment.

[0112] In a general embodiment, the third layer of the multilayer film used in the present invention may be a single layer or a combination of two or more single layers (i.e., a plurality of layers forming the third layer of the multilayer film). Furthermore, the third layer of the multilayer film used in the present invention may be formed from a single polyolefin resin or a blend of two or more polyolefin resins. In one embodiment, the third layer of the multilayer film is formed from, for example, one or more ethylene-based polymer components. In other embodiments, the third layer of the multilayer film comprises a polymer resin blend composition that can be used to manufacture an outer layer identical to the first layer of the multilayer film (e.g., a second outer layer of the multilayer film) or an outer layer different from the first layer of the multilayer film. In other embodiments, the third layer of the multilayer film may be used as at least one inner layer of the multilayer film. When used as an inner layer, in a preferred embodiment, the third layer of the multilayer film may be a sealable skin layer. The third layer (as a second outer layer or inner sealant layer of the multilayer film) may be the same as or different from the first layer (as a first outer layer of the multilayer film).

[0113] Refer again Figure 1 In a preferred embodiment, the polymer resin blend composition used to form the third polyolefin film layer 40 of the multilayer film 10 may be the same polymer resin blend composition as the polymer resin blend composition of the first film layer of the multilayer film; and includes a polymer resin blend composition comprising resin 1 and resin 2; and optionally resin 3. Resin 1, resin 2, and optionally resin 3 have been described above. As an illustration of the invention and not limited thereto, in some embodiments, the polymer resin blend composition is used to manufacture a sealable inner layer as the third film layer of the multilayer film.

[0114] In a general embodiment, the method for producing the at least three-layer multilayer film structure of the present invention includes using any conventional equipment and processes known to those skilled in the art, such as techniques for preparing blown films using blown extrusion, extruded films using co-extrusion, and / or cast films using cast extrusion. Alternatively, the multilayer film structure of the present invention can be produced by incorporating the multilayer film into a laminated structure.

[0115] In some embodiments, when the polymer resin composition contains two or more components for each layer in the layers, the polymer components are first mixed together to form a blend. For example, the individual components can be dry-blended and then uniformly melt-blended in a mixer; or the components can be uniformly mixed directly in a mixer such as a Banbury mixer, Haake mixer, or Brabender internal mixer, or in a single-screw extruder or twin-screw extruder, which may include compounding extruders and side-arm extruders. After the two or more components are mixed to form the polymer blend, the polymer blend is processed into a film structure.

[0116] In some embodiments, for example, the multilayer film can be prepared using a co-extrusion process. In co-extrusion, multiple streams of molten polymer are fed into an annular die (or flat casting) to produce a multilayer film upon cooling. In a preferred embodiment, the first polymer resin blend composition, the second polymer resin blend composition, and the third polymer resin blend composition used to prepare the first layer, the second layer, and the third layer of the multilayer film of the present invention are processed by a blown film process using typical blown film processes and equipment known to those skilled in the art of blown film methods and the art of preparing multilayer films. For example, in one or more embodiments, the process of preparing the multilayer film of the present invention may include forming a blown film bubble by blown film extrusion. In some embodiments, the blown film bubble may be a multilayer blown film bubble. Further according to this embodiment, the multilayer blown film bubble may include at least three layers (the first layer, the second layer, and the third layer of the multilayer film as described herein), and the at least three layers may be adhered to each other. In other embodiments, multilayer films comprising more than three layers, such as five layers, seven layers, etc., can be produced using blown film bubbles.

[0117] In some implementations, for example, blown film bubbles can be formed via a blown film extrusion line, where an extruded film from an extruder die can be formed (blown) and pulled from the tower onto a roll gap. The film can then be wound onto a core. Before winding the film onto the core, the ends of the film can be cut and folded using a folding device, making it difficult to separate the film layers, which may be important for transportation applications or heavy-duty transport bag applications. Other implementations of the blown film process may include the use of a blown film extrusion line having: (1) a length-to-diameter (“L / D”) ratio of, for example, 30 to 1; (2) a blow-up ratio of, for example, 1 to 5; (3) a die with internal bubble cooling; (4) a die gap of, for example, 1 mm to 5 mm; and (5) a film thickness gauge scanner, wherein the total thickness of the multilayer film can be maintained at <1,000 μm, as described above. In one general embodiment, the multilayer blown film bubble formation step can occur, for example, at a temperature of 180°C to 260°C; and the output rate of the process can be, for example, from 10 kg / h to 1,000 kg / h.

[0118] The multilayer films of the present invention exhibit several advantageous properties and benefits superior to those of films previously known in the art. For example, in the preparation of blown films comprising the multilayer films of the present invention, the multilayer films of the present invention exhibit improved performance and mechanical properties, including increased toughness, good dart strength, increased stiffness, good processability, and bubble stability; improved mechanical and damage resistance properties to withstand the forces and loads that the multilayer films of the present invention may experience; and improved impact resistance and tear resistance.

[0119] In some embodiments, when the polymer resin blend composition of at least one layer of the multilayer film contains ZN-AMS-LLDPE resin, in a general embodiment, the layer formed by the composition containing ZN-AMS-LLDPE resin advantageously exhibits at least a 10% increase in toughness strength with respect to dart strength compared to a multilayer film made from a resin composition made from: (1) not containing the ZN-AMS-LLDPE resin of the present invention; (2) containing too much ZN-AMS-LLDPE resin; or (3) containing too little ZN-AMS-LLDPE resin.

[0120] In other embodiments, multilayer films formed from polymer resin blends containing the ZN-AMS-LLDPE resin of the present invention exhibit at least a 15% increase in toughness (or dart strength) compared to multilayer films made from resin compositions not containing the ZN-AMS-LLDPE resin of the present invention; and in still other embodiments, multilayer films formed from polymer resin blends containing the ZN-AMS-LLDPE resin of the present invention exhibit at least a 20% increase in toughness (or dart strength) compared to multilayer films made from resin compositions not containing the ZN-AMS-LLDPE resin of the present invention.

[0121] In yet another embodiment, a multilayer film formed from a polymer resin blend composition containing the ZN-AMS-LLDPE resin of the present invention exhibits a 10% to 50% increase in toughness (or dart strength) compared to a multilayer film made from a resin composition not containing the ZN-AMS-LLDPE resin of the present invention; and even in yet another embodiment, a multilayer film formed from a polymer resin blend composition containing the ZN-AMS-LLDPE resin of the present invention exhibits at least a 10% to 30% increase in toughness (or dart strength) compared to a multilayer film made from a resin composition not containing the ZN-AMS-LLDPE resin of the present invention.

[0122] Other performance characteristics of the multilayer membrane, including tear resistance (in the longitudinal direction (MD) and transverse direction (CD), secant modulus, stiffness and membrane bubble stability, are improved or maintained without adverse effects.

[0123] The improved properties of multilayer films allow for the production of films using less material (“thickness reduction,” i.e., using a thinner film thickness), where the effects of thickness reduction are not detrimental to certain film properties. For example, the physical properties of multilayer films, such as dart / bag drop, puncture resistance, tear resistance, and creep resistance, can be maintained and still meet customer and industrial requirements even with reduced thickness.

[0124] In some embodiments, the multilayer film structure of the present invention can be used to produce end-use products and articles applicable to any number of applications. Exemplary end-uses may include, but are not limited to, multilayer films, multilayer film-based products, and articles manufactured from multilayer films and / or multilayer film-based products, such as for packaging applications. For example, in a preferred embodiment, the multilayer film structure of the present invention is used to produce heavy-duty bags (or heavy-duty transport bags for transportation applications); and the heavy-duty bags are prepared using techniques known to those skilled in the art of bag manufacturing, such as vertical filling and sealing equipment.

[0125] Example

[0126] The following embodiments (Inv.Ex.) and comparative examples (Comp.Ex.) (collectively, “Examples”) are given herein to further illustrate the features of the invention, but are not intended to be construed, explicitly or implicitly, as limiting the scope of the claims. Embodiments of the invention are indicated by Arabic numerals, and comparative examples are indicated by alphabetical letters. The following experiments analyze the performance of embodiments of the compositions described herein. Unless otherwise indicated, all parts and percentages are by weight based on total weight.

[0127] raw materials

[0128] The raw materials / components used in the examples include polymer resins, namely resin AD as described below:

[0129] Resin A

[0130] Resin A (the example of Resin 3) is made by UCAT. TM LLDPE catalyzed by J (a catalyst commercially available from Univin). Resin A is prepared using the following method.

[0131] Preparation of Resin A

[0132] In the presence of ethylene, butene, hydrogen, nitrogen, and isopentane, UCAT TM Catalyst J was injected into the gas-phase polymerization reactor, whereby the reactor contents underwent polymerization to form a polyethylene and butene copolymer. The reaction was carried out under the reactor conditions described in Table I. The resin was then purged under nitrogen to remove residual hydrocarbons. The resin was then compounded with other components using a twin-screw extruder LCM100 and an underwater granulation and cutting hub. The aforementioned other components added to the resin were 600 ppm. 168 and 1,300 ppm Preblend 9K (both additives are available from BASF).

[0133] Resin B

[0134] Resin B (an embodiment of Resin 1) is LLDPE catalyzed by the catalyst disclosed in Invention Example 1a (IE 1a) of WO2019241044, except that the catalyst used to catalyze LLDPE to produce Resin B is prepared on a commercial scale. Resin B is prepared using the following Resin B preparation method.

[0135] Preparation of Resin B

[0136] In the presence of ethylene, butene, hydrogen, nitrogen, and isopentane, a catalyst disclosed in Example 1a (IE 1a) of invention WO2019241044 and produced on a commercial scale was injected into a gas-phase polymerization reactor, whereby the reactor contents underwent polymerization to form a polyethylene-butene copolymer. The reaction was carried out under the reactor conditions described in Table I. The resin was then purged under nitrogen to remove residual hydrocarbons. The resin was then compounded with other components using a twin-screw extruder LCM100 and an underwater granulation and cutting hub. The aforementioned other components added to the resin were 600 ppm. 168 and 1,300 ppm Preblend 9K (both additives are available from BASF).

[0137] Resin C

[0138] Resin C (an embodiment of Resin 1) is LLDPE catalyzed by the catalyst disclosed in Invention Example 1b (IE 1b) of WO2019241044, except that the catalyst used to catalyze LLDPE to produce Resin C is prepared on a commercial scale. Resin C is prepared using the following Resin C preparation method.

[0139] Resin C preparation

[0140] In the presence of ethylene, butene, hydrogen, nitrogen, and isopentane, a catalyst disclosed in Example 1b (IE 1b) of invention WO2019241044 and produced on a commercial scale was injected into a gas-phase polymerization reactor, whereby the reactor contents underwent polymerization to form a polyethylene-butene copolymer. The reaction was carried out under the reactor conditions described in Table I. The resin was then purged under nitrogen to remove residual hydrocarbons. The resin was then compounded with other components using a twin-screw extruder LCM100 and an underwater granulation and cutting hub. The aforementioned other components added to the resin were 600 ppm. 168 and 1,300 ppm Preblend 9K (both additives are available from BASF).

[0141] Resin D

[0142] Resin D (an embodiment of resin 2) has a melt index of 2 g / 10 min and a melt index of 0.923 g / cm³. 3 The low-density polyethylene resin LDPE 450E has a certain density. LDPE 450E is commercially available from Dow Chemical Company.

[0143] The reactor conditions described in Table I are used to prepare resins A, B, and C.

[0144] Table I - Reactor conditions for preparing resins A, B, and C

[0145] <![CDATA[ Conditions / Parameters ]]> <![CDATA[ Resin A ]]> <![CDATA[ Resin B ]]> <![CDATA[ Resin C ]]> Production rate [kg / hour] 4,080 3,220 2,990 Bed weight [kg] 14,180 11,540 14,520 Duration of stay [hours] 3.5 3.6 4.9 Reactor pressure [Pa] <![CDATA[1.68×10 6 ]]> <![CDATA[1.60×10 6 ]]> <![CDATA[1.80×10 6 ]]> Surface gas velocity [m / s] 0.539 0.546 0.533 C2PP[psia] 690,900 690,900 688,100 Bed temperature [°C] 85.6 85.8 85.8 <![CDATA[H2 / C2 ratio [mole / mole]]]> 0.156 0.203 0.259 C4 / C2 ratio [moles / moles] 0.386 0.387 0.344 Al / Ti ratio [moles / moles] 38 117 116 C2 mol% 38.89 40.56 36.16 C4 mol% 14.99 15.69 12.47 <![CDATA[mol% of H2]]> 6.09 8.22 9.33 IC5 Mol% 0.12 0.06 0.17 <![CDATA[mol% of N2]]> 39.98 36.25 42.13

[0146] In Table I above, "C2PP" is the partial pressure of ethylene, "C2" is ethylene, "C4" is 1-butene, and "IC5" is isopentane.

[0147] Some properties of resins A–D are described in Table II, and some properties of resins A–C are described in Table III.

[0148] Table II – Properties of Resin AD

[0149] <![CDATA[ resin ]]> <![CDATA[ MI (grams per minute) ]]> <![CDATA[ Density (g / cc) ]]> <![CDATA[ Comonomer ]]> Resin A 1.8 0.919 1-Butene Resin B 1.8 0.920 1-Butene Resin C 2.0 0.919 1-Butene Resin D 2.0 0.923 -----

[0150] Table III - Properties of Resin AC

[0151]

[0152] Notes to Table III: (1) α = wt% as measured by iCCD method at temperatures ranging from 25.0°C to 37.0°C.

[0153] (2) β = wt% as measured by iCCD method at temperatures ranging from 93.0℃ to 120.0℃.

[0154] (3) γ = via iCCD 方法在 wt%. Measured at temperatures ranging from 75.0℃ to 93.0℃.

[0155] (4) δ = the ratio of wt% measured by iCCD method at 93.0℃ to 120.0℃ to wt% measured at 75.0℃ to 93.0℃.

[0156] (5) Mw = the ratio of the Mw of the fraction eluted from 93.0°C to 120.0°C to the Mw of the whole polymer eluted from 25.0°C to 120.0°C.

[0157] *R 2 These are the linear fit coefficients, calculated using EXCEL linear regression between 0.10 and 0.95 cumulative weight fractions.

[0158] Resin blends

[0159] The polymer resin blend compositions used in the examples comprise three different samples of catalytically catalyzed LLDPE; and the catalysts used to form the catalytically catalyzed LLDPE comprise: (1) a UCAT J catalyst, which forms a catalytically catalyzed LLDPE referred to in the examples as “UCAT J-LLDPE”; (2) a ZN1 catalyst, which forms a catalytically catalyzed AMS-LLDPE; and (3) a ZN2 catalyst, which forms another catalytically catalyzed AMS-LLDPE. Each of the three catalyzed LLDPE resins was blended with an LDPE resin having a MI of 2. The resin blends used in the examples are generally described in Table IV.

[0160] General procedures for preparing resin blends

[0161] The resin components in the described formulations UJ-LDPE, ZN1-LDPE, and ZN2-LDPE are used in the examples; and the percentage of each resin component in the resin components used to prepare the polymer resin blend formulations of the examples is described. The resin components are mixed together at a specified concentration using conventional mixing equipment and processes. Mixing is carried out at room temperature. The resulting blends / mixtures of the resin components (i.e., the prepared polymer resin blend formulations) are then used to fabricate each individual layer of the individual layers in a multilayer film structure.

[0162] The resin blends prepared according to the above procedure are described in Table IV.

[0163] Table IV – Resin Blends

[0164]

[0165] Multilayer film

[0166] Generally, each layer of the three-layer multilayer membranes described in Tables V-VII, i.e., membranes 1-3, is prepared using the various resin blends described above, i.e., blends 1-6. As previously mentioned, a single polymer resin, i.e., resin AD, is used to form polymer resin blends, i.e., blends 1-6, which are then used to form the individual layers of the three-layer membrane structure described in Tables V-VII, i.e., membranes 1-3.

[0167] Table V - Three-layer membranes using various blends 1 (Comparative Example A)

[0168]

[0169] Table VI - Three-layer membrane using various blends 2 (Example 1 of the present invention)

[0170]

[0171] Table VII - Three-layer membranes using various blends 2 (Example 2 of the present invention)

[0172]

[0173] General procedures for manufacturing multilayer films

[0174] The methods for preparing multilayer film structures described in Tables V-VII include the following steps:

[0175] The three-layer multilayer film structures described in Tables V–VII, i.e., samples of membranes 1–3, were manufactured using the Alpine 7-layer blown film line, which includes seven extruders as described in Table VIII. The parameters of the film extruder line are described in Table IX. The 7-layer blown film line was used to form seven film layers; and these seven film layers were used to produce the three-layer multilayer film samples. Each of the seven individual film layers was first produced by each of the seven individual extruders as described in Table VIII; and then the seven layers from the extruders were aggregated together to form a three-layer film structure, which was identified, for example, as the inner, middle, and outer layers of the three-layer multilayer film structure described in Tables V–VII. The parameters of the extruders described in Table IX include operating the extruders at an output rate of 310 psi (141 kg / h) at a melt temperature of 403℉ (206°C) to 480℉ (249°C) (three-layer co-extrusion).

[0176] Processing parameters used in membrane manufacturing

[0177] Table VIII - Alpine Company's 7-layer membrane production line

[0178]

[0179] Table IX - Parameters of Film Extruder Production Line

[0180] Die head size: 9.84 inches (25cm) Die head clearance: 78.7 mils (2mm) Blow-up ratio (BUR): 2.5 Freezing line height 35 inches (89cm) Output rate: 310 lbs / hour (141 kg / hour)

[0181] Measurement and testing methods

[0182] Membrane characterization

[0183] The test standards listed in Table X were used to characterize the membrane structures prepared using the polymer resin formulations described above and used in the examples.

[0184] Table X - Test Standards for Membrane Characterization

[0185] <![CDATA[ Test characteristics ]]> <![CDATA[ standard ]]> ZebedeeTransparency ASTM D1746-15 transparency ASTM D1746-15 Haze ASTM D1003-13 gloss ASTM D2457-21 secant modulus – CD ASTM D882-18 secant modulus – MD ASTM D882-18 Tear: Elmendorf – CD ASTM D1922-15 Tear: Elmendorf – MD ASTM D1922-15 pierce ASTM D5748-95 Dart Impact ASTM D1709-18

[0186] density

[0187] Resin density was measured in isopropanol using the Archimedes displacement method, ASTM D792-13, Method B. Samples used for this test were measured 40 hours after molding and after conditioning for 8 minutes in an isopropanol bath at 23°C to reach thermal equilibrium before measurement. Samples were compressed in a press according to Annex A of ASTM D 4703-16, following Annex A procedure C, with an initial heating period of approximately 190°C for 5 minutes and a cooling rate of 15°C / min. Samples were then cooled in the press to 45°C, with continued cooling until the samples reached room temperature.

[0188] melt flow rate

[0189] Melt flow rate measurements were performed under three different conditions according to the procedure described in ASTM D-1238-03: (1) 190°C and 2.16 kg, (2) 190°C and 5.0 kg, and (3) 190°C and 21.6 kg; and the three melt flow rate measurements were denoted as I2, I5, and I, respectively. 21 As is known to those skilled in the art, melt flow rate is inversely proportional to the molecular weight of the polymer being measured. Therefore, the higher the molecular weight of the polymer, the lower the melt flow rate, but the relationship is not linear. The melt flow rate at 2.16 kg is also referred to herein as the melt index (I2).

[0190] High-temperature gel permeation chromatography

[0191] High-temperature gel permeation chromatography (GPC) was performed on the samples to determine the molecular weight distribution (MWD) and corresponding moments (Mn, Mw, and Mz). The chromatographic system used for GPC measurement was a Polymer Char GPC-IR high-temperature GPC chromatograph (available from Polymer Char, Valencia, Spain), equipped with a 4-capillary differential viscometer detector and an IR5 multi-wavelength infrared detector (available from Polymer Char). A Precision Detectors 2-angle laser scattering detector, model 2040 (available from Precision Detector, now Agilent Technologies), was added to the chromatographic system. A 15-degree angle of light scattering detector was used for computational purposes. Data collection was performed using GPC One software (available from Polymer Char). The system was equipped with an online solvent degassing device (available from Precision Detector, now Agilent Technologies).

[0192] Both the detector and column chambers of the chromatograph were operated at 150°C. The columns used were four PLgel MixedA 7.5 mm × 300 mm 20 μm columns (Agilent Technologies). The chromatographic solvent used was 1,2,4-trichlorobenzene (TCB) containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen injection. The injection volume for each injected sample was 200 μL, and the flow rate was 1.0 mL / min. In other words, the sample was prepared semi-automatically using PolymerChar "Instrument Control" software, with a target sample concentration of 2 mg / mL, and the solvent (containing 200 ppm BHT) was added to a pre-bubbled, septum-capped vial via a PolymerChar high-temperature autosampler. The sample was dissolved at 160°C for 2 hours with "low-speed" shaking.

[0193] For routine molecular weight measurements, GPC column assemblies were calibrated with 21 narrow molecular weight distribution polystyrene standards (available from Polymer Laboratories, now Varian) with molecular weights ranging from 580 to 8,400,000, arranged in a 6-cocktail mixture. For molecular weights ≥1,000,000, 0.025 g of polystyrene standard was prepared in 50 mL of solvent, and for molecular weights <1,000,000, 0.05 g of polystyrene standard was prepared in 50 mL of solvent. The polystyrene standards were dissolved at 80 °C with gentle stirring for 30 minutes. The narrow standard mixture was run first, in descending order starting with the highest molecular weight component to minimize degradation of the standards. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using the following equation (I):

[0194] M 聚乙烯 =A*(M 聚苯乙烯 )^B

[0195] Formula (I)

[0196] In equation (I), “M” is the molecular weight of polystyrene or polyethylene; the value “A” is a positive number < 0.500; and the value “B” equals 1.000. A fifth-order polynomial is used to fit the corresponding polystyrene calibration point. For the entire MWD range from the lowest MW to the highest MW, MWD can also be expressed as an integral of the cumulative weight distribution from zero to 1.00 relative to log(molecular weight) (Streigel et al., Modern Size Exclusion Liquid Chromatography, 2nd ed., p. 450).

[0197] The IR5 detector was calibrated using a quantitative dispensing of at least ten ethylene-based short-chain branched (SCB) polymer standards, with octene used as the comonomer. The polymer properties of the SCB standards are shown in Table XI. Each SCB standard is calibrated in terms of narrow short-chain branching distribution (SCBD) and known comonomer content (e.g., by...). 13The C10 NMR method (measured by Qiu et al., *Analytical Chemistry*, 2009, 81, 8585-8589) was used in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor via a single-point metallocene catalyst. The known monomer content ranged from 0 SCB / 1000 total C in the homopolymer to approximately 40 SCB / 1000 total C, where total C = carbon in the main chain + carbon in the branches. Each SCB standard had a weight-average molecular weight of 36,000 g / mol to 126,000 g / mol, as determined by GPC. Additionally, each SCB standard had a molecular weight distribution (Mw / Mn) of 2.0 to 2.5, as described in Table XI.

[0198] Table XI–SCB Standards

[0199]

[0200]

[0201] Calculate the "IR5 area ratio" (or "IR5 area ratio") of the "baseline-subtracted area response of the IR5 methyl channel sensor" to the "baseline-subtracted area response of the IR5 measurement channel sensor" for each SCB standard (standard filters and filter wheels are supplied by PolymerChar: part number IR5FWM01, included as part of the GPC-IR instrument). 甲基通道面积 / IR5 测量通道面积 The linear fit of the SCB frequency to the IR5 area ratio is constructed in the form of the following equation (II):

[0202] SCB / 1000 total C = A0 + [A1 × (IR5)] 甲基通道面积 / IR5 测量通道面积 )]

[0203] Formula (II)

[0204] Where A0 is the SCB / 1000 total C intercept when the IR5 area ratio is zero, and A1 is the slope of SCB / 1000 total C relative to the IR5 area ratio. A1 represents the increase of SCB / 1000 total C as a function of the IR5 area ratio. For narrow PDI and narrow SCBD standard materials, the IR5 area ratio is equal to the IR5 height ratio.

[0205] A series of chromatograms generated by the "IR5 methyl channel sensor" with "linear baseline subtracted chromatographic height" as a function of column elution volume were constructed to generate baseline-corrected chromatograms (methyl channel). A series of chromatograms generated by the "IR5 measurement channel" of the IR-5 detector with "baseline subtracted chromatographic height" as a function of column elution volume were constructed to generate baseline-corrected chromatograms (measurement channel).

[0206] The “IR5 height ratio” of the “baseline-corrected chromatogram (methyl channel)” and the “baseline-corrected chromatogram (measurement channel)” is calculated at each column elution volume index (each equally spaced index represents 1 data point per second at an elution flow rate of 1 mL / min) within the sample integral range. The IR5 height ratio is multiplied by a coefficient A1, and a coefficient A0 is added to this result to produce the predicted SCB frequency for the sample. The result is converted to comonomer molar percentage using the following equation (III):

[0207] Comonomer molar percentage = {SCB f / [SCB f +((1000-SCB f *Length of comonomer) / 2)]}*100

[0208] Formula (III)

[0209] Among them, "SCB" f "SCB per 1000 total C", and "length of comonomer" is 8, which is the number of carbons in octene.

[0210] The comonomer composition is octene comonomer as reported by MWD. ​​Each elution volume index was converted to a molecular weight value (Mw) using the method described above. i Equation (II) calculates the "comonomer molar percentage (y-axis)" as Log(Mw) value; i The function is used to calculate the slope between the cumulative weight fractions of 0.10 and 0.95. EXCEL linear regression is used to calculate the slope and R-squared value between the cumulative weight fractions of 0.10 and 0.95. 2 (Linear fit coefficient). This slope is defined as the Cumulative Molecular Weight Comonomer Distribution Index (CUMCDI).

[0211] iCCD method

[0212] The term "iCCD" refers to an improved method for comonomer content distribution (CCD) analysis; and is based on the method described in WO2017040127A1. The test method is performed using a Crystallization Elution Fractionation (CEF) instrument (available from PolymerChar) equipped with an IR-5 detector and a bi-angle precision detector (model 2040 light scattering detector, available from Agilent Technologies). o-Dichlorobenzene (ODCB, 99% anhydrous or industrial grade) is used as the solvent. Silica gel 40 (with a particle size of 0.2 mm to about 0.5 mm; available from EMD Chemicals) can be used to dry the ODCB solvent. The dried silica is packed into three empty HT-GPC columns (300 mm × 7.5 mm (ID)) to further purify the ODCB solvent as the eluent. The CEF instrument is equipped with an autosampler with nitrogen (N2) purging capability. Before use, bubble the ODCB with dried N2 for 1 hour.

[0213] Samples were prepared using an autosampler with a concentration of 4 mg / mL (unless otherwise specified) and agitated at 160 °C for 1 hour. The injection volume was 300 μL. The iCCD temperature profiles were as follows: crystallization from 105 °C to 30 °C at 3 °C / min; thermal equilibration at 30 °C for 2 minutes (including a 2-minute elution time for the soluble fraction); elution from 30 °C to 140 °C at 3 °C / min. The sample flow rate during crystallization was 0.0 mL / min. The sample flow rate during elution was 0.50 mL / min. Data were collected at a rate of one data point per second.

[0214] The iCCD column used was a 15cm (length) x 1 / 4 inner diameter (ID) stainless steel tube filled with gold-coated nickel particles (Bright 7GNM8-NiS; available from Nippon Chemical Industrial Co.). The column was filled and conditioned using a slurry method as described in WO2017040127A1. The final pressure for the trichlorobenzene (TCB) slurry filling was 150 bar (10 MPa).

[0215] Column temperature calibration was performed using a mixture of the following substances: (i) 1.0 mg / mL linear homopolymer polyethylene (with zero comonomer content, 1.0 g / cm³). 3 The melt index (I2) and the polydispersity (M) of approximately 2.6 determined by the GPC test method described above. w / M n(ii) polyethylene (a reference material); and (ii) ODCB containing 2 mg / mL eicosane. The iCCD temperature calibration consists of the following four steps: (1) calculating the delayed volume defined as the measured peak elution temperature of eicosane minus the temperature offset between 30.00 °C; (2) subtracting the temperature offset of the elution temperature from the raw iCCD temperature data (note that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.); (3) creating a linear calibration line that converts the elution temperature in the range of 30.00 °C to 140.00 °C, such that the linear homopolymer polyethylene reference material has a peak temperature of 101.0 °C and the eicosane has a peak temperature of 30.0 °C; (4) for soluble fractions measured isothermally at 30 °C, linearly extrapolating elution temperatures below 30.0 °C by using an elution heating rate of 3 °C / min according to the method described in U.S. Patent No. 9,688,795. Use GPCOne software (available from PolymerChar) to generate the SCBD distribution curve dWi / dT, where Wi is the mass of the mass at Ti and T is the calibrated elution temperature.

[0216] Elution fractions, expressed in wt%, are determined within a specific elution temperature range. They are defined as the area of ​​the baseline-subtracted iCCD chromatogram within that temperature range divided by the total integrated area of ​​the baseline-subtracted iCCD elution chromatogram multiplied by 100%. For example, wt% (within the elution temperature range of 75.0°C to 93.0°C) is defined as the area of ​​the baseline-subtracted iCCD chromatogram eluted from 75.0°C to 93.0°C divided by the total integrated area of ​​the iCCD chromatogram (from 25.0°C to 120.0°C) multiplied by 100%.

[0217] Comonomer content relative to iCCD elution temperature was constructed using a solution method with 12 reference materials (ethylene homopolymers and ethylene-octene random copolymers with ethylene equivalent weight-average molecular weights ranging from 35,000 to 128,000, prepared using a single-point metallocene catalyst). All these reference materials were analyzed in the same manner as previously specified (4 mg / mL). The correlation between comonomer molar fraction and elution temperature (T, in degrees Celsius) follows the expression below:

[0218] ln(1-comonomer mole fraction) = -208.328 / (elution temperature + 273.12) + 0.55846.

[0219] Composition Distribution Index (CDBI) is defined as the weight percentage of polymer molecules having a comonomer content within + / - 50% of the median total molar comonomer content (as reported in WO 93 / 03093). The CDBI of polyolefins can be readily calculated from techniques known in the field, such as temperature rising elution fractionation (TREF), for example, SCBD data obtained from temperature rising elution fractionation as described below: Wild et al., Journal of Polymer Science, Poly.Phys.Ed., Vol. 20, 441 (1982); LDCady, “The Role of Comonomer Type and Distribution in LLDPE Product Performance,” SPE Regional Technical Conference, Quaker Square Hilton, Akron, OH, 107-119 (October 1-2, 1985); and U.S. Patents 4,798,081 and 5,008,204.

[0220] In this paper, CDBI is calculated accordingly using the short-chain branching distribution measured by the iCCD method and the comonomer composition correlation with elution temperature as described above.

[0221] By assuming a shape factor of 1 and all virial coefficients equal to zero, the molecular weights of the polymer and polymer fractions were determined directly from a light scattering (LS) detector (precise detector, 90-degree angle) and a concentration detector (IR-5) according to the Rayleigh-Gans-Debys approximation (Striegel and Yau, *Modern Size Exclusion Liquid Chromatogram*, pp. 242 and 263). Baselines from both the LS and concentration detectors were subtracted. An integration window was set to integrate all chromatograms over an elution temperature range (temperature calibration specified above) from 23.0 °C to 120 °C.

[0222] Calculating molecular weight (Mw) using iCCD involves the following steps:

[0223] Step (1): Measure the detector offset (i.e., the volume difference between detectors). The offset is defined as the geometric volume shift between the LS detector and the concentration detector. It is calculated as the difference in elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset using the elution heat rate and elution flow rate. Linear high-density polyethylene (comonomer content of zero, melt index (I2) of 1.0) was used, and polydispersity M2 was obtained by conventional gel permeation chromatography. w / M n (Approximately 2.6). The same experimental conditions as the standard iCCD method described above were used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, followed by 1 minute of thermal equilibration at 137°C as the elution time for the soluble fraction, and elution of the soluble fraction (SF) from 137°C to 142°C at 3°C / min. The flow rate during crystallization was 0.0 mL / min. The flow rate during elution was 0.80 mL / min. The sample concentration was 1.0 mg / mL.

[0224] Step (2): Before integration, each data point in the LS chromatogram is shifted to correct for detector offset.

[0225] Step (3): Integrate the baseline-subtracted LS and concentration chromatograms over the entire elution temperature range of Step (1). The MW detector constant was calculated using known MW HDPE samples in the range of 100,000 to 140,000 Mw and the area ratio of the integrated LS and concentration signals.

[0226] Step (4): The Mw of the polymer was calculated by using the ratio of the integrated light scattering detector (90-degree angle) to the concentration detector and by using the MW detector constant. Using the measured MW detector constant, the NIST NBS1475a was analyzed using the same method as specified in (1) above to obtain a molecular weight of 58,000.

[0227] The Mw ratio is calculated as the Mw of the fraction eluted from 93.0°C to 120.0°C divided by the Mw of the whole polymer (eluted from 25.0°C to 120.0°C).

[0228] Test Results

[0229] Properties of the 3-layer film with mil thickness in Table XII-2

[0230]

[0231] Discussion of Results

[0232] The results described in Table XII show that the three-layer multilayer film structures containing the following polymer resin combinations: ZN1-LLDPE resin and LDPE (Example 1 of the present invention) and ZN2-LLDPE resin and LDPE resin (Example 2 of the present invention) exhibit improved optical and puncture properties compared to the three-layer multilayer film structure containing the polymer resin combination: UJ-LLDPE and LDPE (Comparative Example A). When compared with the resin of Comparative Example A, other properties of the resins of Example 1 and Example 2 of the present invention are maintained (comparable or similar) or improved.

Claims

1. A multilayer film, the multilayer film comprising at least three layers, the at least three layers comprising: (a) At least a first polyolefin film layer, wherein the first polyolefin film layer includes a first outer film layer; (b) at least a second polyolefin film layer, wherein the second polyolefin film layer comprises a core film layer; and (c) At least a third polyolefin film layer, wherein the third polyolefin film layer includes a second outer film layer; wherein the at least third polyolefin film layer is the same as or different from the at least first polyolefin film layer; wherein the at least second polyolefin film layer is disposed between the first polyolefin film layer and the third polyolefin film layer, and separates the first polyolefin film layer from the third polyolefin film layer; wherein the first polyolefin film layer, the second polyolefin film layer and the third polyolefin film layer are in contact with each other to form at least a three-layer film structure; At least one of the polyolefin film layers in the multilayer film is prepared from a polymer blend composition comprising: (i) at least a first ethylene-based polymer resin, said at least a first ethylene-based polymer resin comprising a catalyzed linear low-density polyethylene resin prepared using a spray-dried Ziegler-Natta catalyst system, said catalyst system comprising a spray-dried particulate solid consisting of hydrophobic fumed silica, MgCl2 and tetrahydrofuran, said catalyst system further comprising Ti(OiPr)4 and dichloroethylaluminum; and (ii) At least a second ethylene-based polymer resin; wherein the at least second ethylene-based polymer resin comprises low-density polyethylene resin.

2. The multilayer membrane of claim 1, wherein at least one of the polyolefin membrane layers of the multilayer membrane comprises a catalyzed linear low-density polyethylene resin prepared using the spray-dried Ziegler-Natta catalyst system; and wherein the multilayer membrane comprising a polyolefin membrane layer of a catalyzed linear low-density polyethylene resin prepared using a Ziegler-Natta catalyst different from the spray-dried Ziegler-Natta catalyst system exhibits at least a 10% improvement in puncture resistance compared to the puncture resistance of a multilayer membrane comprising a polyolefin membrane layer comprising a polyolefin membrane layer of a catalyzed linear low-density polyethylene resin prepared using the spray-dried Ziegler-Natta catalyst system.

3. The multilayer membrane according to claim 1, wherein the catalyzed linear low-density polyethylene is a copolymer of ethylene and 1-butene, and is catalyzed using the spray-dried Ziegler-Natta catalyst system.

4. The multilayer membrane according to claim 1, wherein one or more of the first polyolefin film layer, the second polyolefin film layer, and the third polyolefin film layer of the multilayer membrane are independently polyolefin film layers prepared from a polymer resin blend composition of the following substances: (i) at least a first ethylene-based polymer resin; wherein the at least first ethylene-based polymer resin comprises a catalyzed linear low-density polyethylene resin prepared using the spray-dried Ziegler-Natta catalyst system; and (ii) At least a second ethylene-based polymer resin; wherein the at least second ethylene-based polymer resin comprises low-density polyethylene resin.

5. The multilayer film according to claim 1, wherein the catalyzed linear low-density polyethylene resin prepared using the spray-dried Ziegler-Natta catalyst system has a melt index (MI) of 0.8 g / 10 min to 2.8 g / 10 min and 0.910 g / cm³, as determined by ASTM D 1238-03 at 190 °C and 2.16 kg. 3 Up to 0.935 g / cm 3 The density; and the low-density polyethylene resin of said multilayer film has a melt index of 0.5 g / 10 min to 2.5 g / 10 min and 0.916 g / cm³, as determined by ASTM D 1238-03 at 190 °C and 2.16 kg. 3 Up to 0.940 g / cm 3 The density.

6. The multilayer membrane according to claim 1, wherein the catalyzed linear low-density polyethylene resin of the multilayer membrane is: (a) formed from a butene comonomer used to form a poly(ethylene-co-1-butene) copolymer resin; (b) prepared by a gas-phase method using the spray-dried Ziegler-Natta catalyst system; and (c) has a density of 0.910 g / cm³. 3 Up to 0.935 g / cm 3 (d) density; having a melt index of 0.8 g / 10 min to 2.8 g / 10 min as determined by ASTM D 1238-03 at 190 °C and 2.16 kg; (e) having a Mw / Mn ratio greater than 3.0; (f) having a Mz / Mw ratio greater than 2.5; (g) having a cumulative molecular weight comonomer distribution index of less than 0.1; (h) having the weight percentage eluted from 93.0 °C to 120.0 °C in the range of 0.13 to 0.26 as determined by iCCD. Divide by the weight percentage eluted from 75.0°C to 93.0°C; (i) optionally, the weight percentage eluted from 25.0°C to 37.0°C in the range of 6.0% to 8.0% as determined by iCCD; (j) optionally, the weight percentage eluted from 75.0°C to 93.0°C greater than 41.5% as determined by iCCD; and (k) optionally, generated using a Ziegler-Natta pre-catalyst system prepared by a gas-phase method.

7. The multilayer film according to claim 1, wherein the low-density polyethylene resin of the multilayer film structure has: (a) a density of 0.915 g / cc to 0.925 g / cc; and (b) a melt index of 0.8 g / 10 min to 2.5 g / 10 min as determined by ASTM D 1238-03 at 190 °C and 2.16 kg.

8. The multilayer film according to claim 1, wherein the multilayer film has a density of 1.15 × 10⁻⁶ as determined by ASTM D5748-95. 7 J / m 3 Up to 1.75 × 10 7 J / m 3 The puncture resistance value within the range.

9. The multilayer membrane according to claim 1, wherein the thickness of the at least first polyolefin membrane layer accounts for 20% to 40% of the total membrane structure; wherein the thickness of the at least second polyolefin membrane layer accounts for 20% to 60% of the total membrane structure; and wherein the thickness of the at least third polyolefin layer accounts for 20% to 40% of the total membrane structure.

10. The multilayer membrane according to claim 1, wherein each of the at least first polyolefin membrane layer, the at least second polyolefin membrane layer and the at least third polyolefin membrane layer is a single layer or multiple layers.

11. A packaging article for use in packaging applications, the packaging article comprising a multilayer film according to claim 1.

12. The packaging article according to claim 11, wherein the packaging article is a heavy-duty packaging bag.

13. A method for producing a multilayer film according to claim 1, the method comprising bringing at least three film layers into contact together, the at least three film layers comprising: (a) At least a first polyolefin film layer, wherein the first polyolefin film layer includes a first outer film layer; (b) at least a second polyolefin film layer, wherein the second polyolefin film layer comprises a core film layer; and (c) At least a third polyolefin membrane layer, wherein the third polyolefin membrane layer comprises a second outer membrane layer; wherein the at least third polyolefin membrane layer is the same as or different from the at least first polyolefin membrane layer; wherein the at least second polyolefin membrane layer is disposed between the first polyolefin membrane layer and the third polyolefin membrane layer, and separates the first polyolefin membrane layer from the third polyolefin membrane layer; wherein the first polyolefin membrane layer, the second polyolefin membrane layer and the third polyolefin membrane layer are in contact with each other to form at least a three-layer membrane structure; and wherein at least one of the polyolefin membrane layers in the at least three-layer membrane structure is prepared from a polymer composition containing at least one ethylene-based polymer resin, the at least one ethylene-based polymer resin comprising a catalyzed linear low-density polyethylene resin prepared using a spray-dried Ziegler-Natta catalyst system, the catalyst system comprising a spray-dried particulate solid consisting of hydrophobic fumed silica, MgCl2 and tetrahydrofuran, the catalyst system further comprising Ti(OiPr)4 and dichloroethylaluminum.

14. A polymer resin blend composition for preparing the multilayer film according to claim 1, wherein the polymer resin blend composition comprises a blend of two or more polyethylene-based polymer resins, said two or more polyethylene-based polymer resins comprising: (i) at least a first ethylene-based polymer resin, said at least a first ethylene-based polymer resin comprising a catalyzed linear low-density polyethylene resin prepared using a spray-dried Ziegler-Natta catalyst system, said catalyst system comprising a spray-dried particulate solid consisting of hydrophobic fumed silica, MgCl2 and tetrahydrofuran, said catalyst system further comprising Ti(OiPr)4 and dichloroethylaluminum; and (ii) At least a second ethylene-based polymer resin, said at least a second ethylene-based polymer resin comprising low-density polyethylene resin.

Citation Information

Patent Citations

  • Lldpe-LDPE blown film blend

    US20130245201A1

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Interpolymers of ethylene and unsaturated carboxylic acids

    US4599392A